Toxicological Study of n-hexane and Chloroform Extracts of Lantana camara L. in Experimental Animals - Dash, Sribatsa Lanchhana; Mohapatra, Ranjit; Mekap, Suman Kumar; Masanta, Smruti Ranjan; Katiyar, Arpit; Sharma, Nitin; Karwasra, Ritu; Mishra, Sagar Kumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The aim of the current study is to investigate the acute, sub-acute and sub-chronic toxicity study of extracts (n-hexane and chloroform) of L. camara in Wistar rats. Materials and Methods: HPTLC and GC-MS analysis were carried out to analyze different constituents present in L. camara extract. Acute toxicity study was conducted as per OECD 420 guidelines, while sub-acute and sub-chronic studies were conducted according to OECD 407 and 408 guidelines respectively. Toxicopathological effects of both extracts were tested with the help of hemotoxylin and eosin staining of vital organs (liver, kidney, brain, testes, and ovaries) in experimental animals. Antioxidant and behavioral tests were also conducted on both the extracts, so as to evaluate the possible effects of toxicity. Results: The toxicity investigation of chloroform and n-hexane extracts exhibits no toxicity in terms of hematological (p<0.01) and biochemical parameters (p<0.05). Histopathological sections also confirmed the non-toxic effects on the liver, brain, kidney and on reproductive organs. Conclusion: The n-hexane and chloroform extracts of L. camara can be safely used for therapeutic purposes.
Keywords: Lantana camara; GC-MS; HPTLC; Toxicity; Histopathology; Antioxidant; PI uptake